2017
DOI: 10.5334/gjgl.310
|View full text |Cite
|
Sign up to set email alerts
|

Spoken syntax in a comparative perspective: The dative and genitive alternation in varieties of English

Abstract: This paper introduces a new resource designed to facilitate the quantitative investigation of syntactic variation in spoken language from a comparative perspective. The datasets comprise homogeneously annotated collections of "interchangeable" (i.e. competing) genitive and dative variants in four varieties of English: American English, British English, Canadian English, and New Zealand English. To showcase the empirical potential of the data source, we present a suggestive analysis that investigates the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 38 publications
(56 reference statements)
1
20
1
Order By: Relevance
“…Later studies have confirmed these findings while adding further nuance. The semantics of the verb arguments also plays a role [12], and there is agreement that, on the whole, the dative alternation is subject to broadly similar constraints across different macro-varieties of English [2,[13][14][15][16][17].…”
Section: Verbsemtagmentioning
confidence: 99%
See 2 more Smart Citations
“…Later studies have confirmed these findings while adding further nuance. The semantics of the verb arguments also plays a role [12], and there is agreement that, on the whole, the dative alternation is subject to broadly similar constraints across different macro-varieties of English [2,[13][14][15][16][17].…”
Section: Verbsemtagmentioning
confidence: 99%
“…Despite this activity, the dative alternation continues to draw theoretical and empirical attention in linguistics, with a number of relevant and underexplored questions remaining. These include questions of linguistic prototypicality [16], the role of probability in spoken grammar [17], and the role of individual-level sociolinguistic factors [2].…”
Section: Verbsemtagmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature has recently emerged from the incorporation of the principles of probabilistic grammar into the World Englishes paradigm with the aim of exploring and delimiting the extent to which the strength of probabilistic constraints fluctuates across varieties of English (e.g. Rosenbach 2002, 2003; Hinrichs & Szmrecsanyi 2007; Bresnan & Hay 2008; Szmrecsanyi & Hinrichs 2008; Bresnan & Ford 2010; Bernaisch et al 2014; Szmrecsanyi et al 2016; Heller et al 2017; Röthlisberger et al 2017; Szmrecsanyi et al 2017; among others). Common to most of these studies is the observation that varieties share a fairly robust probabilistic grammar in that the constraints affecting a particular syntactic phenomenon are largely stable across varieties and fuel the same kind of syntactic choices.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This approach allows one to see whether X 1 , X 2 , …, X n behave differently depending on L1 or VARIETY (see Gries and Deshors 2014: Section 3), which is often the main question of such studies (even if this is often not discussed using the above kind of statistical-interaction terminology). As mentioned above, such studies are becoming increasingly widespread; examples include but are not limited to Deshors (2014Deshors ( , 2018, Wulff et al (2014), , Szmrecsanyi et al (2017). In spite of the fact that these studies are a huge improvement over decades of monofactorial chisquared or loglikelihood ratio tests, depending on one's perspective, Gries and Deshors (2014) and Gries and Adelman (2014) developed an alternative approach that has a slightly different focus.…”
Section: General Introductionmentioning
confidence: 99%